Feeding habits of harp and hooded seals in Greenland waters - Kapel, Finn O (NAMMCO Scientific Publications, 2000)
Results of stomach contents analyses of harp and hooded seals collected in West Greenland waters in the period 1986-1993 are reviewed, and compared with published data and circumstantial information from local hunters. The diet of harp seals in this region is variable but consists mainly of pelagic crustaceans (Thysanoessa spp. and Parathemisto libellula) and small fish species like capelin (Mallotus villosus), sandeel (Ammodytes spp.), polar cod (Boreogadus saida) and Arctic cod (Arctogadus glacialis). Species of importance for commercial fisheries in Greenland, such as Northern prawn (Pandalus borealis), Atlantic cod (Gadus morhua), and Greenland halibut (Reinhardtius hippoglossoides) play a minor role in the diet of harp seals in this area. Variation in the diet of hooded seals is less well documented, but in addition to the species also taken by harp seals, larger demersal fishes like Greenland halibut, redfish (Sebastes spp.), cod, and wolffish (Anarhichas minor) are apparently important prey items.